Promoting Security Intelligence in Preventing Conflicts Between Pencak Silat Colleges in the Jombang Police Jurisdiction (Indonesian Journal of Police Studies, 2024)
In East Javanese society, conflict between silat schools is still a social phenomenon that often occurs. This conflict not only has an impact on tensions between universities, but also causes significant material losses, such as damage to houses, vehicles and the environment. In fact, this conflict can result in loss of life for the victims involved. Therefore, this research aims to eliminate all forms of conflict between pencak silat schools and improve public order in Jombang Regency. In order to achieve this goal, this research carries out several relevant concepts and theories. The concepts of optimization, intelligence gathering, crime prevention and persecution are the main basis for this research. Apart from that, management theory, SWOT analysis, collaboration and police operational guidelines are also used as a framework for resolving conflicts that occur. The results of this research show that intelligence gathering has a significant impact in preventing conflict. However, there are several factors that hinder the optimality of this collection. Therefore, it is necessary to develop organizational resources, increase coordination and collaboration between related agencies, as well as implement optimal fundraising methods to achieve the desired goals. Thus, efforts to overcome conflicts between silat schools in East Java require good cooperation and coordination between various related parties.
Keywords: Kata Kunci: Konflik, Penggalangan, Pencak Silat